2011
DOI: 10.1515/jpem.2011.013
|View full text |Cite
|
Sign up to set email alerts
|

The energy expenditure of an activity-promoting video game compared to sedentary video games and TV watching

Abstract: Background-Screen time continues to be a major contributing factor to sedentariness in children. There have been more creative approaches to increase physical over the last few years. One approach has been through the use of video games. In the present study we investigated the effect of television watching and the use of activity-promoting video games on energy expenditure and movement in lean and obese children. Our primary hypothesis was that energy expenditure and movement decreases while watching televisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
(26 reference statements)
4
13
0
1
Order By: Relevance
“…They found that among children aged 13–15 years old, EE was significantly higher than when playing sedentary videogames. Similar results were found by Leatherdale et al, 22 Mitre et al 21 and White et al 20 who all compared Nintendo Wii activities to sedentary screen-time activities in children. Lanningham-Foster et al 18 measured EE in adults and children while playing Nintendo Wii boxing, playing a sedentary videogame, watching TV, standing, sitting and while at rest.…”
Section: Resultssupporting
confidence: 80%
“…They found that among children aged 13–15 years old, EE was significantly higher than when playing sedentary videogames. Similar results were found by Leatherdale et al, 22 Mitre et al 21 and White et al 20 who all compared Nintendo Wii activities to sedentary screen-time activities in children. Lanningham-Foster et al 18 measured EE in adults and children while playing Nintendo Wii boxing, playing a sedentary videogame, watching TV, standing, sitting and while at rest.…”
Section: Resultssupporting
confidence: 80%
“…Many studies have demonstrated the ability of “exergames” to increase energy expenditure in children (Lanningham-Foster et al, 2006; Graves et al, 2008; Barkley and Penko, 2009; Siegel et al, 2009; Mitre et al, 2011; White et al, 2011) but unfortunately this does not always translate into the likelihood children will be motivated to play an “exergame” over a sedentary game. Our research illustrates that there can be a discordant relationship between the greater energy expenditure of an “exergame” and a lower motivation to play the game in the presence of a peer.…”
Section: Discussionmentioning
confidence: 99%
“…Since girls have been shown to be less physically aggressive than boys, it is possible that girls found boxing to be too combative (Maccoby and Jacklin, 1980). Wii boxing was chosen due to the potential for greater energy expenditure compared to other games (Mitre et al, 2011; Roemmich et al, 2012). The game for the sedentary video game was also a boxing game, which allowed us to compare sedentary boxing to physically interactive boxing with two players.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported on the impact of "active" video games, but the findings were mixed. Two studies reported increased physical activity levels among active video game users compared with traditional video game users and participants in a traditional physical education class [57,58]. Conversely, neither Baranowski et al [59] nor Owens et al [60] found evidence that active video games increased overall physical activity among children compared with controls.…”
Section: Prevention Interventionsmentioning
confidence: 98%